2021
DOI: 10.1002/nafm.10570
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Methods Used to Estimate Growth Parameters from Subsampled Age Data

Abstract: Due to time and resource limitations, the growth of many fish species is evaluated with age and length data in a length‐stratified subsample of a sample from a population. Some fisheries professionals draw inferences about growth using age and length data from only those fish that were actually aged (aged‐only method). Alternatively, growth may be evaluated by employing a method of incorporating the length‐stratified aged subsample with information from the entire sample of fish collected, such as the weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This may be due to the added logistical complexity of setting up and operating such a sampling approach or the need to understand population-level length composition in order to inform a POS sampling approach. Such length composition data are also needed to apply a weighted ALK which may correct for bias from FOS (Kimura, 1977;Goodyear, 2019;Lusk et al, 2021). Our models assumed that samples were available for the upper and lower size bins for FOS, but in reality, the largest and smallest individuals are not regularly encountered in many fisheries, and significant sampling effort would need to be allotted to obtain them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the added logistical complexity of setting up and operating such a sampling approach or the need to understand population-level length composition in order to inform a POS sampling approach. Such length composition data are also needed to apply a weighted ALK which may correct for bias from FOS (Kimura, 1977;Goodyear, 2019;Lusk et al, 2021). Our models assumed that samples were available for the upper and lower size bins for FOS, but in reality, the largest and smallest individuals are not regularly encountered in many fisheries, and significant sampling effort would need to be allotted to obtain them.…”
Section: Discussionmentioning
confidence: 99%
“…FOS sets a predetermined number of samples for each length bin (Chang et al, 2019), a strategy which has been shown to lead to overestimates of mean length-at-age and L ∞ (Goodyear, 1995;Chih, 2009a;Coggins Jr et al, 2013;Goodyear, 2019). Biased growth parameter estimates associated with FOS may be corrected by applying an age-length key (ALK; Lusk et al, 2021;Goodyear, 2019). Problematically, ALKs require informed assumptions regarding the numbers at length in a fish population, which are likely lacking for data-poor fisheries in need of growth studies.…”
Section: Introductionmentioning
confidence: 99%